Inhibition of histone H3K27 demethylase selectively modulates inflammatory phenotypes of natural killer cells - Cribbs, A; Hookway, E; Wells, G; Lindow, M; Obad, S; Oerum, H; Prinjha, R; Athanasou, N; Sowman, A; Philpott, M; Penn, H; Soderstrom, K; et al. (American Society for Biochemistry and Molecular Biology, 2018)
Natural killer (NK) cells are innate lymphocytes, important in immune surveillance and elimination of stressed, transformed, or virus-infected cells. They critically shape the inflammatory cytokine environment to orchestrate interactions of cells of the innate and adaptive immune systems. Some studies have reported that NK cell activation and cytokine secretion are controlled epigenetically, but have yielded only limited insight into the mechanisms. Using chemical screening with small-molecule inhibitors of chromatin methylation and acetylation, further validated by knockdown approaches, we here identified Jumonji-type histone H3K27 demethylases as key regulators of cytokine production in human NK cell subsets. The prototypic Jumonji domain–containing protein 3 (JMJD3/UTX) H3K27 demethylase inhibitor GSK-J4 increased global levels of the repressive H3K27me3 mark around transcription start sites of effector cytokine genes. Moreover, GSK-J4 reduced IFN-γ, TNFα, granulocyte–macrophage colony-stimulating factor (GM-CSF), and IL- 10 levels in cytokine-stimulated NK cells, while sparing their cytotoxic killing activity against cancer cells. The anti-inflammatory effect of GSK-J4 in NK cell subsets, isolated from peripheral blood or tissue from individuals with rheumatoid arthritis (RA), coupled with an inhibitory effect on formation of bone-resorbing osteoclasts, suggested that histone demethylase inhibition has broad utility for modulating immune and inflammatory responses. Overall, our results indicate that H3K27me3 is a dynamic and important epigenetic modification during NK cell activation and that JMJD3/UTX-driven H3K27 demethylation is critical for NK cell function.